Environmental Health Inspection of Public Facility Locations in the Working Area of Puskesmas Gandasuli - Nurintani, Nurintani; Fauzi, Murti; Lestari, Tutik; Suharto, Suharto; Andiani, Andiani; Supriyatni, Nani; Sumiati, Tati; Iriyani, Julfa Ida; Sanusi, Nurnia; Patisausiwa, Aulia (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
To ensure that the school environment remains healthy and students have healthy lifestyles, school environment inspections are necessary. According to the law, every child in Indonesia is entitled to a healthy, safe, and comfortable school environment. The goal of school health is to ensure that students' life skills can be enhanced in a healthy environment, where they can learn comfortably and grow optimally to become high-quality individuals. This community service aims to identify environmental sanitation risks in public facilities, particularly schools. The method used was direct observation of the school's condition using the previously prepared IKL form, followed by interviews with relevant parties to reinforce the findings. The results still found several schools with conditions that do not meet health standards. It is hoped that with the implementation of school environmental health inspections, the school authorities will improve in providing adequate school facilities to realize a healthy school. It is hoped that with the implementation of school environmental health inspections, the school authorities will improve in providing adequate school facilities to realize a healthy school.